Non-alcoholic fatty liver disease in a patient with maturity onset diabetes in the young - Masih, Izhaq (BMJ Publishing Group, 2009)
We present the case of a 34-year-old man who was first seen in our clinic in 2003. His α-glutamyl transferase (GGT) was raised but the rest of the liver function tests (LFTs) and liver screen were normal. He was diagnosed with maturity onset diabetes of the young (MODY) when he was 21 years old. Abdominal ultrasound showed fatty liver disease. Liver biopsy in 2006 showed non-alcoholic fatty liver disease (NAFLD). This combination has rarely been described in the medical literature. Metformin and gliclizide was started and weight reduction advised. Despite this there is no change in his LFTs, and in 2008, his GGT concentration was even higher. This condition is challenging because of the limited treatment options. Globally, NAFLD is rising and complications such as liver cirrhosis can be seen commonly. NAFLD in a patient with MODY needs thorough attention.